Democracy in the Age of Globalization and Mediatization - Kriesi, H. (Challenges to Democracy in the 21st Century, 2013)
This book provides comprehensive coverage of the models of contemporary democracy; its social, cultural, economic and political prerequisites; its empirically existing varieties and its two major challenges - globalization and mediatization. The book also covers the global spread of democracy and its spread into supranational democracies.